Analysis Of Domestic Tourist Satisfaction And Loyalty In Penglipuran Tourism Village, Bangli - Artha Putra, I Nengah Sandi; Arini, Ni Nyoman; Raditya, I Putu Tiana (Politeknik Internasional Bali, 2023)
Penglipuran Tourism Village is an independent tourist village that has been developing since 1993. In its development, tourist behavior is very important to know. Two important aspects that must be known are tourist satisfaction and loyalty. In tourism marketing studies, there are many aspects that influence satisfaction and loyalty, including tourist motivation and destination attributes. Analyzing tourist behavior is very important as an evaluation step and a sustainable marketing strategy. The aims of this research are 1) to analyze the influence of motivation and destination attributes on tourist satisfaction, 2) to analyze the influence of motivation and destination attributes on tourist loyalty, 3) to analyze the influence of tourist satisfaction on tourist loyalty. This research was designed using quantitative methods which aim to analyze the size of the correlation and causal relationship between variables and justify the significance of each hypothesis. One hundred domestic tourists who have visited are the samples in this study. The sample was determined using accidental sampling by distributing questionnaires online via Google Form. Data were analyzed using SEM (Structural Equation Modeling) with SmartPLS software version 3.0. The research results show that 1) motivation does not have a significant effect on tourist satisfaction. Destination attributes have a significant effect on tourist satisfaction, 2) motivation does not have a significant effect on tourist loyalty. Destination attributes do not have a significant effect on tourist loyalty, 3) tourist satisfaction has a significant effect on tourist loyalty. Through the findings of this research, it can be used as reference material for sustainable marketing in looking at the behavior of domestic tourists who visit the Penglipuran Tourism Village.